Anisotropic interfacial properties of monolayer GeSe—metal contacts. (27th August 2019) - Guo, Ying; Pan, Feng; Ren, Yajie; Wang, Yangyang; Yao, Binbin; Zhao, Gaoyang; Lu, Jing
Abstract: Monolayer germanium selenide (ML GeSe) has been experimentally fabricated recently. It is a new member of the two-dimensional (2D) semiconductor material group and shares a similar pucker structure, direct band gap, anisotropy, and high carrier mobility with isoelectronic ML phosphorene. Additionally, it had an advantage over phosphorene in that it is intensely ambiently stable and thus more suitable for a channel material for next-generation high-performance transistors. We systematically research the contact properties between ML GeSe and electrodes (Cu, Ag, Ti, Au, Pd, Pt, graphene and graphene-Cu) in a transistor configuration by using first-principle and quantum transport calculations. ML GeSe field effect transistors (FETs) have strong Fermi level pinning and anisotropic Schottky contacts in the lateral interface. Graphene electrodes have a dramatic lateral p -type (quasi- p -type) ohmic contact in the b ( a )-axis direction of ML GeSe FETs, and graphene-Cu hybrid electrodes have a quasi- p -type ohmic contact in the a -axis direction. Hence, high performance can be achieved in ML GeSe FETs with graphene electrodes or via the insertion of graphene between the ML GeSe and a Cu electrode.